Nature Imagery in Non-Green Advertising: The Effects of Emotion, Autobiographical Memory, and Consumer's Green Traits. Issue 4 (1st October 2016) - Hartmann, Patrick; Apaolaza, Vanessa; Eisend, Martin
Abstract : Images of pristine nature constitute frequent elements of visual advertising design. Research on the effectiveness of such imagery has been scarce, however. Which psychological processes are involved? Do all individuals react equally to nature advertising imagery? Based on environmental psychology theory, the present research analyzes the effectiveness of the use of nature imagery in non-green advertising and the underlying processes involved. We conduct three experimental studies, two with student samples and one with a representative population sample, to test the effects of visual advertising stimuli featuring nature versus urban and indoor scenery. Findings contribute to research in two ways: First, emotional ad responses that are similar to the feelings experienced in nature as well as the retrieval of positive autobiographical memories are identified as intervening processes by which nature advertising imagery increases attitude toward the ad (Aad) and brand (Abr). Second, results indicate these processes are moderated by consumers' green traits, with green consumers being more susceptible to the persuasive effects of nature advertising imagery even though advertisements were non-green. The processes are further moderated by the accessibility of memory of past nature experiences. These findings enrich our knowledge on the effects of specific visual appeals and provide practical implications for visual advertising effectiveness.